Pengaruh Fintech, Perilaku Keuangan dan Persepsi Kemudahan Terhadap Pengambilan Keputusan oleh Mahasiswa untuk Melakukan Pinjaman Online - Ronadi, Violina Jasmine; Permatasari, Anita (BIP's JURNAL BISNIS PERSPEKTIF, 2025)
ABSTRACT ABSTRACT The variables used in this research are financial technology, financial behavior and perceived convenience which can influence students' decision making to take out online loans. The data used in this research is primary data obtained from questionnaires. The results of this research are that financial technology influences students' decision making to take out online loans. The results of the second research in this study are that financial behavior influences students' decision making to take out online loans. The third research result is that the perception of convenience has no influence on students' decision making to take out online loans. Keywords: Financial Technology, Financial Behavior, Perception of Convenience, Online Loans